A RARE TUMOR – ADRENAL ANGIOSARCOMA: (case report) - Kumar M., A.; Roy, N.; Jafri, H.; Popli, V.; Karthik, V. S.; Phuntsho, T. (International Journal of Medicine and Medical Research, 2023)
Background. Primary adrenal angiosarcoma is an exceptionally rare tumor with an incidence of <1% of soft tissue sarcomas. Less than 50 cases being described in literature; most of them were nonfunctional presenting with symptoms of abdominal lump, weight loss, fatigue or weakness. The treatment remains multi-modal with involvement of surgeon as well as medical oncologist. Objective. The aim of this case report is to describe an entity which is rare in terms of incidence. It was functional as well as metastatic and managed with multimodality therapy. Methods. The case is a 47-year-old man diagnosed with metastatic adrenal angiosarcoma. The patient was managed with chemotherapy followed by surgery. Results. The final histopathological examination of the specimen and immunohistochemistry revealed angiosarcoma. At present the patient is under follow-up. Conclusion. Even though surgery forms the main stay of management, the role of multi-modality therapy forms the cornerstone for adrenal angiosarcomas.